HRM Strategy in Improving Employee Performance of PT. AICE Bangkalan - Maslahatun Kamilah; Siti Anisah; Khoirul Anam; Iriani Ismail (Formosa Journal of Applied Sciences, 2023)
definition of human resource management is a system whose aim is to influence the behavior and attitudes of human resources to be able to provide maximum contribution in achieving organizational goals. Employee performance refers to the work results that have been achieved by an employee or group of individuals in accordance with the responsibilities and authority given to them. This includes various aspects such as the amount of work completed, quality of work, punctuality, workplace attendance, and cooperative work attitude. In this case, PT AICE Bangkalan has demonstrated a strong commitment to improving the performance of its employees through various HR management strategies that have been implemented. To ensure that HR management runs in accordance with predetermined plans and strategies, the company has formulated General Directorate & HR Program Targets as a guide in its implementation